Gaya kepemimpinan ekspatriat Korea-China dan manajer lokal di perusahaan multinasional dan permasalahan yang dihadapi - Ardiansyah, Giri Teguh; Hardiyanti, Hardiyanti; Anne, Lisye Ira; Heikal, Jerry (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2024)
The globalization process occurring in various countries demands cultural acculturation and leadership models and styles at the global workplace or at the company level. Various cultures that have significantly entered Indonesia include Chinese and South Korean cultures, mainly because these companies have invested in Indonesia. This research aims to determine the leadership styles of Korean-Chinese expatriates and local managers in multinational companies PT. X, PT. Y, and PT. Z when facing issues related to individual culture, personality, behavior, and differing beliefs, as well as when understanding the problems faced by Korean-Chinese expatriate leaders and local managers within multinational companies PT. X, PT. Y, and PT. Z in Indonesia. Based on the data analysis presented, it can be concluded that the cross-cultural leadership style of expatriates in PT. X, PT. Y, and PT. Z is employee-centered (democratic). The leadership style applied by expatriates in PT. X and local managers from PT. Y is seen in decision-making, leader roles, and delegation of authority. The role of expatriate leaders is performed by providing control in completing employee tasks, directing and controlling employees, and constantly monitoring the progress of assigned tasks to ensure they are completed quickly to achieve the company's targets, which are common goals at PT. X, PT. Y, and PT. Z.